Hubungan Nilai Progress Test Dan Indeks Prestasi Mahasiswa Angkatan 2017 Fakultas Kedokteran Dan Ilmu Kesehatan Universitas Warmadewa - Widiantari, Putu Ayu Krisna; Ningrum, Rima Kusuma; Ekayani, Ni Wayan Diana (PendIPA Journal of Science Education, 2024)
Two assessment systems in education are summative assessment and formative assessment. One example of a formative assessment is the progress test which is carried out once a year at the Faculty of Medicine and Health Sciences (FKIK) at Warmadewa University. The progress test aims to determine the extent to which competencies have been mastered by students, stimulate long-term retention and stimulate deep learning behavior. This study aims to determine the relationship between progress test scores and grade points of 2017 FKIK Warmadewa University students. This research is an analytical study with a cross-sectional design. The population in this study were 95 students of the 2017 FKIK Unwar class, 76 people fulfill the inclusion criteria and 2 people were excluded based on exclusion criteria so that the final population was 74 people. The study uses secondary data including progress test scores, odd semester social studies and GPA. Secondary data will be processed using the SPSS application. The results of the bivariate analysis showed that there was a significant relationship (p<0.05) between the score of the progress test and the achievement index with a weak strength level (r=0.20-0.39), moderate (r=0.40-0.59) to very strong (r=0.80-1). The average grade 2017 progress test score is 31.2. The average grade point average for odd semester 2017 students is 3.49. The cumulative grade point average for the 2017 class is 3.47. Suggestions that can be given are for students to take the exam seriously so that the progress test scores can describe their cognitive abilities.